Macroeconomics - Lieberman, Marc (Thomson/South-Western, 2008)
This book's concise, less is more approach has been carefully crafted in terms of both content and supporting pedagogy to keep students focused on learning and applying the central ideas used in economic analysis. It uniquely employs a simple methodology throughout to emulate how economists look at problems, and teaches students how to use this same analytical process in developing their own economic analysis skills. Hall/Lieberman's careful focus on core theoretical ideas as well as systematically applying the theoretical tools to interesting real-world questions conveys the message that economics is an integrated, powerful body of knowledge that can be used to address important issues